Potential of sugarcane tolerant to white leaf disease to increase profitability in Thai sugarcane production - Jarnkoon, Varinthon; Kladsuwan, Lawan; Klomsa-ard, Peeraya; Sriroth, Klanarong; Anusonpornperm, Somchai; Sreewongchai, Tanee; Ngoenklan, Ratchadawan (Agriculture and Natural Resources, 2025)
Importance of the work: Sugarcane white leaf (SCWL)-tolerant sugarcane has the potential to significantly reduce crop losses and increase profits in Thailand’s sugarcane production. Objectives: This research aimed to evaluate the potential of SCWL-tolerant sugarcane varieties compared to Khon Kaen 3 (KK3) sugarcane, which is preferred by farmers. Materials and Methods: Real-time PCR targeting the secA gene was used to quantify the phytoplasma causing SCWL in sugarcane. Electron microscopy techniques were used to confirm the presence of the phytoplasma in phloem tissues. Finally, the impact of SCWL on sugarcane yield, CCS, and the incidence of SCWL symptoms were evaluated after harvest. Results: Seven days after phytoplasma inoculation of KK3, MPT16-110, MPT01-956, MPT04-204, and MPT12-618 by Matsumuratettix hiroglyphicus (Matsumura), MPT12-618 consistently maintained the lowest infection level throughout the year, while KK3 showed the highest infection. At 12 months, MPT12-618 had significantly higher sugarcane yields than the other varieties. Varieties showed no significant differences in sweetness. However, MPT16-110 was the sweetest (9.90 ± 0.17), followed by MPT12-618 (9.60 ± 0.54), MPT04-204 (9.28 ± 0.33), MPT01-956 (9.21 ± 0.29), and KK3 (8.70 ± 0.31). Electron microscopy techniques showed that KK3 had thinner sieve plates in its phloem tissue compared to the MPT varieties. MPT varieties exhibited lower SCWL symptoms (10–15%) during the tillering phase compared to KK3 (25%). Main finding: Compared to KK3, sugarcane variety MPT12-618 exhibited lower levels of phytoplasma infection from 2 to 12 months, and a lower incidence of SCWL symptoms in the tillering phase of the first ratoon.